Dopamine and glutamate release in the dorsolateral caudate putamen following withdrawal from cocaine self-administration in rats - Gabriele, Amanda (2012)
Evidence suggests that cocaine addiction may involve progressive neuroadaptive changes in the dorsolateral caudate putamen (dlCPu). While cocaine seeking following abstinence from chronic self-administration requires intact dlCPu function, in vivo neurotransmitter release in the dlCPu has not been investigated. The current study measured dlCPu dopamine (DA) and glutamate (GLU) release during drug seeking following limited or extended abstinence, as well as in response to a cocaine priming injection alone. Male, Sprague–Dawley rats self-administered cocaine (0.2 mg/50 μl infusion, i.v.) for 10 days (2 h/day). In vivo microdialysis occurred in the self-administration chamber after 1 and 14 days of abstinence (Experiment 1). A separate set of animals that completed self-administration as well as drug naïve controls received a cocaine priming injection (20 mg/kg) during concurrent microdialysis (Experiment 2). DA release increased during drug seeking in the self-administration context at both 1 and 14 days post abstinence. In contrast, GLU release only increased after 1 day of abstinence. Furthermore, animals with a cocaine self-administration history showed enhanced DA and GLU release following cocaine challenge as compared to drug naïve controls. These results indicate that chronic cocaine self-administration enhances dlCPu DA and GLU under both drug-paired context and drug-primed conditions.